ITI with high-dose FIX and combined immunosuppressive therapy in a patient with severe haemophilia B and inhibitor - Beutel, K.; Hauch, H.; Rischewski, J.; Kordes, U.; Schneppenheim, J.; Schneppenheim, R. (Hämostaseologie, 2009)
Inhibitor development is a rare but serious event in hemophilia B patients. Management is hampered by the frequent occurrence of allergic reactions to factor IX, low success rates of current inhibitor elimination protocols and the risk of development of nephrotic syndrome. Single cases of immune tolerance induction (ITI) including immunosuppressive agents like mycophenolat mofetil (MMF) or rituximab have been reported. We present a case of successful inhibitor elimination with a combined immune-modulating therapy and high-dose factor IX (FIX). This boy had developed a FIX inhibitor at the age of 5 years and had a history of allergic reactions to FIX and to FEIBA→. Under on-demand treatment with recombinant activated FVII the inhibitor became undetectable but the boy suffered from multiple joint and muscle bleeds. At the age of 11.5 years ITI was attempted with a combination of rituximab, MMF, dexamethasone, intravenous immunoglobulins and high-dose FIX. The inhibitor did not reappear and FIX half-life normalized. No allergic reaction, no signs of nephrotic syndrome and no serious infections were observed.
Keywords: Haemophilia B; inhibitor; immune tolerance induction; immunosuppression